A Mediterranean paradigm? Convergence and divergence in the Southern European Health Care Systems - Guido Giarelli (Faculdade de Medicina de Botucatu (Unesp), 2021)
The concept of a 'Mediterranean paradigm' was raised by Josep Figueras in 1994 as a distinctive Southern European model for the health care systems of Italy, Spain and Greece based on the basis of six factors. The subsequent debate (including Portugal, too) is reconstructed on the basis of pros and cons arguments. The specific contribution of the author to the debate - consisting in the proposal of the concept of 'health macro-region' as an analytic tool to pursue a more comprehensive approach in comparative terms on the basis of a connectionist model - is then presented in details by showing the peculiar characteristics of the Southern European health macro-region. Finally, an historical perspective involving three different kinds of temporality (long, middle and short span) is proposed in order to explain both the substantial similar timing (diachronic convergence) and, at the same time, the significant differences (synchronic divergences) among Southern European health care systems in the way and levels their national health services were implemented.